Perencanaan Struktur Gedung Pusat Rehabilitasi Narkotika Kota Langsa - Ramadani, Putri; Purwandito, Meilandy; Fajri, Haikal (Universitas Ibn Khaldun, 2024)
The Narcotics Rehabilitation Center Building is a much needed facility for every drug addict who needs rehabilitation. For the safety and comfort of building users structural element planning is required to determine the correct dimensions and reinforcement. The planning was carried out in Langsa City, where the SDS and SD1 values were 0,79 and 0,8 so that the seismic category fell into E. The working loads were dead load, live load, and earthquake load. The regulations used are SNI 2487-2019 concerning Structural Concrete Requirements for Buildings and Explanations, SNI 1726-2019 concerning Procedures for Earthquake Resistance Planning for Building and Non Building Structures, SNI 1727-2020 concerning Minimum Design Loads and Related Criteria for Buildings and Other Structures, SNI 2052-2017 concerning Concrete Reinforcing Steel. Structural analysis and structural modeling using the ETABS 2018 program. This plan uses 2 types of dilation with an L shaped building. The results and design analysis show that the column dimensions are 65/65 cm for K1, 55/55 cm for K2, and 60/60 cm for K3. The beam dimensions are 50/70 for Main Beam 1. 45/65 cm for Main Beam 2, 40/60 cm for Main Beam 3, and 30/45 cm for Child Beam. The dimensions of the floor plate are 15 cm thick and the roof plate is 12 cm. Key words: Response Spectrum, Reinforced Concrete, SRPMK, Design, ETABS